2021
DOI: 10.1002/mnfr.202100163
|View full text |Cite
|
Sign up to set email alerts
|

Disposition of Dietary Polyphenols in Breast Cancer Patients’ Tumors, and Their Associated Anticancer Activity: The Particular Case of Curcumin

Abstract: Scope Some polyphenol‐derived metabolites reach human breast cancer (BC) tissues at concentrations that induce cell senescence. However, this is unknown for isoflavones, curcuminoids, and lignans. Here, their metabolic profiling in normal (NT) and malignant (MT) mammary tissues of newly‐diagnosed BC patients and the tissue‐occurring metabolites’ anticancer activity are evaluated. Methods and results Patients (n = 26) consumed 3 capsules/day (turmeric, red clover, and flaxseed extracts plus resveratrol; 296.4 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
53
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(55 citation statements)
references
References 51 publications
2
53
0
Order By: Relevance
“…Under the same conditions, their free forms (quercetin, Uro-A, IsoUro-A, and Uro-C) effectively decreased 5-HETE, LTB 4 , PGE 2 , HKE 2 , and HKD 2 levels in a dose-dependent manner. Although the free forms are hardly found in the bloodstream, their presence in inflammatory environments is conceivable via deconjugation, as described for luteolin, quercetin, resveratrol, Uro-A, and curcumin [ 77 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Under the same conditions, their free forms (quercetin, Uro-A, IsoUro-A, and Uro-C) effectively decreased 5-HETE, LTB 4 , PGE 2 , HKE 2 , and HKD 2 levels in a dose-dependent manner. Although the free forms are hardly found in the bloodstream, their presence in inflammatory environments is conceivable via deconjugation, as described for luteolin, quercetin, resveratrol, Uro-A, and curcumin [ 77 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 ].…”
Section: Resultsmentioning
confidence: 99%
“…The flavonoid glycoside rutin (quercetin-3-rutinoside) acts as a precursor (via deglycosylation) of quercetin in the colon [ 74 ], whereas curcumin and flavanones (such as the glycoside hesperidin and its aglycone hesperetin) can be detected in the colon for hours in their original form [ 75 , 76 ]. Upon absorption, the (poly)phenolic compounds and the microbial metabolites undergo phase-II metabolism to form conjugated molecules (glucuronides, sulfates, and methyl esters), which are the main molecules detected in the bloodstream, intestinal tissues, bile, feces, urine, and different systemic tissues [ 77 , 78 ]. Animal and human metabolism and bioavailability studies have reported that, at the intestinal level, the parental phenolic compounds (which serve as substrates of the gut microbiota) and their microbial-derived metabolites can achieve concentrations from μM to mM.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Orally administered resveratrol, like other polyphenols, has poor bioavailability and is converted into a wide variety of metabolites. Growing evidence highlights that mainly glucuronide and sulfate conjugates metabolites of resveratrol are the molecules that could reach systemic human tissues [69,70]. Ávila-Gálvez et al showed, that in normal and malignant mammary tissues from breast cancer patients major metabolites of resveratrol are resveratrol-3-O-sulfate and dihydro resveratrol-3-O-glucuronide.…”
Section: Discussionmentioning
confidence: 99%
“…In breast cancer cells and tissues exposed to CUR, it has been shown to decrease ER expression, leading to decreased cell proliferation, migration, invasion, and angiogenesis, while increasing apoptosis, cell cycle arrest, and senescence in breast cancer cell lines [93][94][95]. In clinical trials, CUR has been shown to slightly reduce fatigue in women with advanced, metastatic breast cancer and can be used as an anti-oxidation, anti-cancer agent that does not compromise the therapeutic efficacy of radiotherapy [96][97][98][99].…”
Section: Phytoestrogens: Plant-derived Chemicalsmentioning
confidence: 99%